Vaccination against autoimmune diseases moves closer to the clinic - Willem van Eden (Taylor & Francis Group, 2020)
Biologicals, e.g. TNF inhibitors, have improved dramatically the efficacy of medical interventions in autoimmune diseases, such as in rheumatoid arthritis (RA). However, although progressive inflammation can be halted in this way, no drug-free remissions or lasting cures are reached. For this to become real, therapies based on induction antigen-specific immune tolerance are sought. This review describes mechanisms of tolerance and the current possibilities for induction of therapeutic tolerance through antigen-specific vaccination approaches. And despite the fact that for various diseases the search for appropriate autoantigens is ongoing, pioneering studies are now already developed that use more broadly inflammation associated antigens. Through their capacity to preferentially induce regulatory T cells, heat shock proteins are an attractive source of such broadly inflammation associated antigens.